Formulation of Anti-Blackhead Rubber Mask from Purified Gambier (Uncaria gambir [Hunter] Roxb.) - Agustin, Rini; Akrami, Hafizatul; Syafni, Nova (Fakultas Farmasi Universitas Andalas, 2023)
The purified was isolated from Uncaria gambir [Hunter] Roxb. that contains more than 90% of catechins. Its antioksidant and antibacterial properties have potential to formulate as cosmetics. Dry form formulation of cosmetic was one approach to minimize cathecins degradation in a product. In this study, three formulation of rubber mask containing 5% of purified gambier was done. . Each formulation was formulated with calcium sulfate, propylene glycol, magnesium carbonate, citrus essential oil and variation of HPMC and chitosan as film former. The three formulas had a brown color, smooth textures, the gambier odor, visually homogeneous, particle sizes at 112.24 – 116.39 µm, moisture values at 3.9 – 7.04%, pH of 6, drying times of 8 to 15 minutes, adhesive power of > 10 seconds and remained stable for 21 days at 4±2°C and 27±2°C. The actual catechin content in formula I, II, and III were 0.89%, 1.09%, and 1.39%, respectively. The best formula was formula III, which contained 40% HPMC and 10% chitosan due to the fastest drying time of 8.36 minutes ± 19 seconds and the highest catechins content at 1.39%.The purified was isolated from Uncaria gambir [Hunter] Roxb. that contains more than 90% of catechins. Its antioksidant and antibacterial properties have potential to formulate as cosmetics. Dry form formulation of cosmetic was one approach to minimize cathecins degradation in a product. In this study, three formulation of rubber mask containing 5% of purified gambier was done. . Each formulation was formulated with calcium sulfate, propylene glycol, magnesium carbonate, citrus essential oil and variation of HPMC and chitosan as film former. The three formulas had a brown color, smooth textures, the gambier odor, visually homogeneous, particle sizes at 112.24 – 116.39 µm, moisture values at 3.9 – 7.04%, pH of 6, drying times of 8 to 15 minutes, adhesive power of > 10 seconds and remained stable for 21 days at 4±2°C and 27±2°C. The actual catechin content in formula I, II, and III were 0.89%, 1.09%, and 1.39%, respectively. The best formula was formula III, which contained 40% HPMC and 10% chitosan due to the fastest drying time of 8.36 minutes ± 19 seconds and the highest catechins content at 1.39%.